Kombinované řešení časné tracheobronchopleurální píštěle po pravostranné sleeve pulmektomii - Hanuliak, J; Szkorupa, M; Chudáček, J; Stašek, M; Neoral, Č (Rozhledy v chirurgii, 2017)
Extended tracheo-bronchoplastic resection for lung cancer with carinal involvement ranks among technically demanding procedures. Despite certain progress in oncological therapy, this type of resection remains the only potentially curative treatment of NSCLC in this localization. However, given the severity of complications postoperative mortality is relatively high (711%). The main cause of death is tracheobronchopleural fistula complicated by thoracic empyema, bronchopneumonia and septic shock. If ARDS (acute respiratory distress syndrome) develops, the mortality rate rises up to 70%. The treatment of tracheobronchopleural fistula is arduous, long-term and essentially multidisciplinary. In this case report, the authors present the case of a 58 years old patient developing the tracheobronchopleural fistula early after carinal resection and sleeve pneumonectomy for a centrally localised squamous cell carcinoma of the right lung. The fistula was primarily sutured and secured using a muscular flap. For recurrence of the fistula, tissue adhesive glue was applied in combination with the introduction of a plastic stent, which resulted in healing of the tracheobronchopleural fistula.Key words: sleeve pulmonectomy carinal resection tracheobronchopleural fistula tracheobronchial stenting.
Keywords: pooperační komplikace; Carcinoma, Non-Small-Cell Lung; Middle Aged; lidé; Pneumonectomy; píštěle; pneumektomie; Fistula; Humans; Postoperative Complications; nemalobuněčný karcinom plic; lidé středního věku; lokální recidiva nádoru; Lung Neoplasms; nádory plic; Neoplasm Recurrence, Local